Distribution and potential involvement of PTEN in the innate immune response during viral infections in Cherry Valley ducks - Chen, Wende; Han, Shaojie; Li, Rong; Li, Shuo; Cao, Zhi; Pan, Qing; Li, Gen (Frontiers in Immunology, 2025)
IntroductionPhosphatase and tensin homolog (PTEN) is a well-established tumor suppressor gene that antagonizes the PI3K/AKT signaling pathway and plays a critical role in regulating both innate and adaptive immune responses. However, its function in avian species, particularly in ducks, remains largely unexplored.MethodsIn this study, the full-length cDNA of duck PTEN (duPTEN) was cloned from the spleen of healthy Cherry Valley ducks. Sequence alignment and phylogenetic analysis were performed to evaluate its structural conservation and evolutionary relationships. The tissue distribution of duPTEN mRNA was examined using quantitative real-time PCR (qRT-PCR). Furthermore, duPTEN expression was assessed in the spleen, lung, and brain at 1, 3, and 5 days post-infection (dpi) following exposure to Duck Tembusu Virus (DTMUV), Duck Plague Virus (DPV), and Novel Duck Reovirus (NDRV).ResultsSequence analysis demonstrated that duPTEN shares a high degree of conservation with PTEN from other avian species, displaying 100% identity with sequences from Gallus gallus and Meleagris gallopavo. qRT-PCR results revealed that duPTEN is ubiquitously expressed across multiple tissues, with the highest expression observed in the brain. Upon DTMUV and DPV infection, duPTEN expression was significantly upregulated in the spleen and lung but downregulated in the brain. In contrast, NDRV infection led to consistent downregulation of duPTEN across all three tissues.DiscussionThis study is the first to characterize the molecular cloning, tissue-specific expression, and virus-induced regulation of duPTEN in ducks. The findings suggest that duPTEN plays a role in the host immune response to diverse viral infections, highlighting its potential involvement in the regulation of antiviral innate immunity in avian species.